Nursing process: factors that difficult and factors that facilitate the teaching - Dell'Acqua, Magda Cristina Queiroz; Miyadahira, Ana Maria Kazue (Revista da Escola de Enfermagem da USP, 2000)
The present study intends to identify how the teaching nursing process in the Graduation Schools of the São Paulo State are presented. The population was composed of 247 docents. As part of the methodology a questionnaire was elaborated. It was sent to 899 docents of the 32 public and private nursing schools of the São Paulo State. The results demonstrated that the factors that difficult the teaching of the nursing process were bigger in number than the factors that facilitate. However, the teaching of the nursing process, despite the presented difficulties, has been offered to the teachers of public and private schools of the São Paulo State.